Pharmaceutical intervention on Ca2+/cAMP signaling interaction: benefits for combating neurodegeneration and diseases related to aging - Afonso Caricati-Neto; Leandro Bueno Bergantin (International Journal of Human Anatomy, 2017)
This review explores crosstalk between Ca2+ and cAMP signaling and its therapeutic implications for neurodegeneration and aging. It summarizes candidate interventions and translational challenges.
Keywords: Ca2+/cAMP Signaling